Raising awareness: people are your last line of defence. Issue 11 (November 2017) - Mansfield-Devine, Steve
Abstract : Many organisations view their own people as a threat. Whether deliberately or accidentally, members of staff certainly have the potential to cause serious cyber-security incidents. On the other hand, people can often spot problems and deal with them, in a way that even the most advanced technology can't. When your firewalls, intrusion prevention systems and other defences fail, people are your last line of defence. But, as Amy Baker, VP of marketing at Wombat Security Technologies, explains in this interview, this works only if you give them the necessary training and support and provide leadership from senior executives who are also properly trained. Many organisations view their own people as a threat. On the other hand, people can often spot problems and deal with them in a way that even the most advanced technology can't. When your technological protections fail, people are your last line of defence. But, as Amy Baker of Wombat Security Technologies explains in this interview, this works only if you give them the necessary training and support and provide leadership from senior executives.